Online Geometry theorems, problems, solutions, and related topics.
Geometry Problem. Post your solution in the comment box below.Level: Mathematics Education, High School, Honors Geometry, College.Click the diagram below to enlarge it.
Observe that ΔABC is a 30°-60°-90° triangle, and so are ΔAHB, ΔHBD, ΔHMD. Also observe that HBDM is a kite. Let BN⊥AC at N which is the mid-point of GE. Let EP⊥BC at P which is the mid-point of DF. Let AG=a. ThenAB = AH + HB = 2 AG + GH = (2+√3)aBC = 2 ED + DM = 3 AG + 2 GH = (3+2√3)aAE = AG + GH = (1+√3)aHence, AE = BC − AB
Join the collinear points H, O, D.The three 60-30-90 Right Triangles AHG, HDB, HDM are congruent to one another.Let each side of the equilateral triangle be "a" and each side of the square be "b".So BD = DM = a - b. Also HB = HM = b, AH = 2AG = 2BD = 2DM = 2a - 2b.Follows AB = AH + HB = (2a - 2b) + b = 2a - b, AE = AG + GE = (a - b) + b = awhile BC - AB = (BD + DC) - AB = [(a - b) + 2a] - [2a - b] = a.Hence AE = BC – AB.(Incidentally AB = BF and AE = FC)
Also: angle CAF = 15 degree
Let BA meet FE in N. Let the side of the square be a and let AG = b. Easily Tr. EFC is isoceles with FC = a+b. Now H, O, D are collinear and by congruent Tr.s easily we can prove that HB = a and BD = b. So BC = 2a+3b. Now since < BNF = 30, Tr. AEN is isoceles and AN = a+b, AH = 2b and HB = a. So BN = 2a+3b = BC.So AN + AB = BC hence BC - AB = AN = AE.(Note that a = sqrt3 X b which I have avoided using to maintain clarity)Sumith PeirisMoratuwaSri Lanka